Restructuring urban planning to facilitate sustainable consumption - Samson, Caroline; Freudendal-Pedersen, Malene (Frontiers in Sustainability, 2022)
Food, mobility, and housing are essential and fundamental to human life. At the same time, these consumption areas have the highest climate impact. To achieve a higher degree of climate-friendly consumption, radical changes in everyday practices of food, mobility, and housing are needed. In this paper, empirical data demonstrates that time is perceived as a limited resource in everyday life which drives (un)sustainable practices. Through discussions of the perception of time and related practices, it becomes visible that urban mobility planning connects specific food and housing practices through an understanding of historical and contemporary urban planning supporting time efficiency. This indicates that rethinking urban forms and infrastructure can provide frames that can restructure everyday practices to become more sustainable. To exemplify this, the 15-minute city concept is used as a speculative example of how to restructure everyday practices and facilitate a planning approach that is aligned with sustainable consumption.